Kemampuan hambat ekstrak temulawak (Curcuma xanthorrhiza Roxb.) terhadap adhesi bakteri Streptococcus mutans - Erin Imaniar B; Sri Kunarti; Widya Saraswati (Conservative Dentistry Journal, 2017)
Background : Streptococcus mutans is the most cariogenic microorganism in the oral cavity. Streptococcus mutans has the ability to use dietary carbohydrates, such as sucrose, to synthesize extracellular polysaccharides (glucan and fructan) through glucosyltransferase and fructosyltransferase. Extracellular polysaccharide has a role in promoting the adhesion of bacteria. Chlorhexidine  is the gold standard as antiplaque agent but chlorhexidine is not fully able to inhibit the adhesion of bacteria because it has an effect that can increase gtfC and gtfD expression on S. mutans in planktonic form. Temulawak extract (Curcuma xanthorrhiza Roxb.) contains of curcumin, xanthorrhizol, saponin, flavonoid and tannin that have an effect to inhibit activity and secretion of glucosyltransferase and fructosyltransferase. Purpose: The aim of this study is to find out the ability of temulawak extract (Curcuma xanthorrhiza Roxb.) to inhibit adhesion of Streptococcus mutans.  Method: This study was designed as an experimental laboratory study with post test only control group design using Streptococcus mutans. Temulawak was extracted using maceration method. The number of bacteria that can perform adhesion to the tooth surface can be determined by performing calculations using formulas plate count method. Result: Temulawak extract (Curcuma xanthorrhiza Roxb.) at concentrations of 25%, 37.5%, 50% and chlorhexidine can inhibit bacterial adhesion of Streptococcus mutans. Conclusion: Temulawak extract at concentration of 50% and 37.5% has the best ability to inhibit the adhesion of bacteria among other treatment groups.